Increased Incidence of Total Knee Replacement Surgery in Patients With Psoriasis: A Secondary Cohort Analysis of a Nationwide, Population-Based Health Claims Database - Lu, Ming-Chi; Fan, Kuo-Sheng; Hsu, Chia-Wen; Koo, Malcolm; Lai, Ning-Sheng (Frontiers in Medicine, 2021)
Patients with rheumatic diseases, such as rheumatoid arthritis, ankylosing spondylitis, and systemic lupus erythematosus, have increased risk of receiving total knee replacement surgery or total hip replacement surgery. We speculated that psoriasis could also attack the joints of the knees and hips, leading to an increased risk of receiving total knee replacement surgery or total hip replacement surgery. The aim of this study was to investigate the risk of total knee replacement or total hip replacement surgery in patients with psoriasis using a nationwide, population-based health claims database in Taiwan. Using the Taiwan’s National Health Insurance Research Database, we identified 10819 patients with psoriasis between 2000 and 2012. A comparison cohort consisting of five patients without psoriasis for each patient with psoriasis was assembled, based on frequency matching for sex, 10-year age interval, and index year. Both groups were followed until a diagnosis of the study outcomes (total knee replacement or total hip replacement surgery) or the end of the follow-up period. Incidence rate ratios (IRRs) for the outcome variables were calculated using multiple Poisson regression models. Female patients with psoriasis exhibited a significantly higher incidence of receiving total knee replacement surgery (adjusted IRR=1.44, p=0.014)). Analyses stratified by age groups showed that the risk of receiving total knee replacement surgery was significantly higher older (adjusted IRR=1.31, p=0.047) patients with psoriasis. There were no significant differences in the risk of receiving total hip replacement surgery in patients with psoriasis compared with controls, either with or without stratification by sex or age groups. In conclusion, patients with psoriasis were associated with an increased risk of receiving total knee. Clinicians should be vigilant in assessing the presence of arthritis in these patients, and initiate strategies to delay or prevent the need for joint replacement.